Demanding Equal Inheritance Rights For Women: Tension Among Shari’a and Tunisia’s New Constitution 2014 - Budi Juliandi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
President Essebsi (2017) approved the law of gender equality in inheritance in Tunisia. Instead of gaining public appreciation of Islam, this achievement was seen as contrary to sharia. This research seeks to address whether or not there could be a common ground between applying sharia and gender equality through an examination of sharia regarding inheritance, and, finally, an attempt to show the relationship between sharia and the Tunisia’s constitution of 2014 in responding to social change. The paper argues that in spite of the constitution’s progressive language, women still face legal discrimination in their ability to inherit because of sharia.